Enhanced removal of perfluoroalkyl substances using MMO-TiO2 visible light photocatalyst - Yang, Heejin; Park, Seong Jik; Lee, Chang Gu (Alexandria Engineering Journal, 2024)
Exploration of easily produced visible light photocatalysts is still necessary. Thus, this study investigated the catalytic performance of a mixed metal oxide-titanium dioxide (MMO-TiO2) to remove perfluorooctanoic acid (PFOA), a typical and harmful perfluoroalkyl substance, under visible light conditions. Analysis of degradation efficiencies revealed that MMO-TiO2 exhibited a remarkable removal efficiency of 95.99 ± 1.49 %, surpassing other catalysts, including TiO2, ZnAl, MMO, and ZnAl-TiO2. MMO-TiO2, derived from ZnAl-TiO2 calcination, displayed a 5.66-fold higher apparent degradation rate constant (1.07 × 10−2 min−1) compared to ZnAl-TiO2 (1.89 × 10−3 min−1). These materials were characterized via X-ray powder diffractometry, Fourier transform infrared-attenuated total reflectance, N2 adsorption-desorption analysis, and field emission-scanning electron microscopy. Results revealed that O2•- radicals play a pivotal role as the predominant species that mediate PFOA removal. Comparative experiments using probe compounds confirmed increased O2•- production during MMO-TiO2 photoreaction under visible light. In addition, this study explored the effect of operational parameters, such as catalyst dose, initial PFOA concentration, solution pH, and water matrices on the photocatalytic removal process. These findings provide insight into the removal of PFOA using MMO-TiO2, highlighting the potential of this visible light catalyst for the eco-friendly removal of persistent organic pollutants in aquatic systems.
Keywords: Fluorinated organic compound; Light conditions; MMO-TiO2; Operational variables; Perfluoroalkyl substances; Perfluorooctanoic acid; Visible light; Visible light condition; Visible-light photocatalysts; ]+ catalyst; Fluorinated organic compound; MMO-TiO2; Operational variables; Photocatalysis; Visible light condition